Toward a qualitative architecture; a phenomenological study of the Gothenburg museum of art - Karlsson, Emil (My University, 2021)
The Gothenburg Museum of Art is, after one hundred years of service presently in need of renovations and an extension. The museum’s location was and still is revealing of the city’s interest in physical representative space but also the important function and status of the museum as a cultural institution. The role is in a large degree not only cultural but also social, economic, and political. An architectural project of this magnitude cannot contently be made simply of factors such as form and function but must be expanded by critical questions of architecture’s role, scope and ultimately meaning. This thesis aims to determine how phenomenological notions of place can illuminate and determine questions regarding architectural discourse beyond concrete physical factors. To test the hypothesis that the phenomenological place can add to our practical projects in architecture, a study was made of the theories in architectural discourse mainly by Christian Norberg-Schulz and Martin Heidegger. Simultaneously an inventory of Götaplatsen and Gothenburg Museum of Art was made engaging with questions of meaning in various levels of the city and building. These two studies were then combined in a discussion and analysis. The concept of place and architecture was shown as not having a fixed meaning and must be interpreted on a case-by-case basis. The modern society is in a large degree affected by calculative thought and strives for efficiency rather than qualitative authenticity. The results suggest that a deeper meaning of architecture lies not in a fixed absolutism and efficiency but in an understanding of it as authentically concerned concretization of our existential being-in-the-world.